Preservice Music Teachers’ Soundscape Memories as Indicators of Musical Eco-Literacy - Hakanpää, Tua; Paananen, Pirkko; Ervasti, Marja (Sage, 2026)
This study investigates preservice music teachers’ meaningful soundscape memories and how these
memories reflect students’ general musical eco-literacy. We ask: Do sound memories reflect the factors
in the Paananen model of eco-literacy? A theory-driven content analysis was performed based on the
Paananen model’s competency categories. The data entries were analyzed using repeated measures
analysis of variance. Fleiss’ kappa was used to check for inter-rater agreement. The competency areas
of the Paananen model of eco-literacy in music were present in the university students’ narratives of
meaningful soundscape memories. Recognition of eco-literacy from the soundscape narratives was
statistically significantly different between the different competency factors, F(3.37, 236.00) = 71.79,
p < .001, partial η2 = .51. Meaningful soundscape memories as written assignments emphasize the
cognitive and emotional competency factors in the eco-literate musical thinking of preservice music
teachers. A large proportion of the sound memories reflected a strong sense of connection to the
natural environment, was positively connected to nature, and depicted a concrete, specific location.
Therefore, soundscape memories could be a pedagogical tool for promoting place-specific ecoliteracy
in the musical sense and in the sense of living an eco-literate life.